Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s00299-011-1208-6
|View full text |Cite
|
Sign up to set email alerts
|

Roles of reactive oxygen species in methyl jasmonate and nitric oxide-induced tanshinone production in Salvia miltiorrhiza hairy roots

Abstract: Salvia miltiorrhiza is one of the most popular traditional Chinese medicinal plants for treatment of coronary heart disease. Tanshinones are the main biological active compounds in S. miltiorrhiza. In this study, effects of exogenous methyl jasmonate (MJ) and nitric oxide (NO) on tanshinone production in S. miltiorrhiza hairy roots were investigated and the roles of reactive oxygen species (ROS) in MJ and NO-induced tanshinone production were elucidated further. The results showed that contents of four tanshin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…ROS brings about peroxidation of membrane lipids, which leads to membrane damage and the unbalancing of cell homeostasis which can, in extreme cases, lead to cell death (one of possible defence mechanisms) (Pérez-Pérez et al 2012). Enhanced H 2 O 2 and O 2 -production was also detected in Salvia militrirrhiza hairy roots (Liang et al 2012) or Panax ginseng roots (Ali et al 2006). A similar trend of rapid H 2 O 2 accumulation (24 and 48 h after MeJA application) was observed in Arabidopsis protoplasts (Zhang and Xing 2008).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…ROS brings about peroxidation of membrane lipids, which leads to membrane damage and the unbalancing of cell homeostasis which can, in extreme cases, lead to cell death (one of possible defence mechanisms) (Pérez-Pérez et al 2012). Enhanced H 2 O 2 and O 2 -production was also detected in Salvia militrirrhiza hairy roots (Liang et al 2012) or Panax ginseng roots (Ali et al 2006). A similar trend of rapid H 2 O 2 accumulation (24 and 48 h after MeJA application) was observed in Arabidopsis protoplasts (Zhang and Xing 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Thereafter, morphological changes in mitochondria and chloroplasts suggested the presence of ROS mediated alteration of membranes. Moreover, studies with antioxidant enzymes (catalase and superoxide dismutase) and natural antioxidant (ascorbic acid) added prior to MeJA treatment showed alleviation in ROS production (Liang et al 2012;Zhang and Xing 2008). Thus, it could be suggested that the modulation of intercellular ROS levels, mainly H 2 O 2 , may act as a mediator in MeJA signalling cascade (Orozco-Cárdenas et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Exogenous MeJA, nitric oxide, abscisic acid, polyethylene glycol-induced drought, and Ag + have been shown to trigger a burst of reactive oxygen species (ROS) in SMHR (Liang et al 2012). ROS may act as a regulatory factor for various biological reactions, such as for example epidermal cell death.…”
Section: The Antioxidant Response To Ye and Ag + Stressmentioning
confidence: 98%
“…The hairy root culture system is a valuable tool for plant molecular biology research (Guo et al 2013;Gao et al 2014) and SMHR produced from leaf explants infected with Agrobacterium rhizogenes were shown to be able to make tanshinones and salvianolic acids. The observation that yeast extract (YE) and AgNO 3 (Ag + ) dramatically increased tanshinone production in SMHR (Liang et al 2012), led to research where a cDNA library of SMHR induced by YE and Ag + containing 25 793 non-redundant isotigs was built (Gao et al 2014). However, we still know little about the cellular events through which these stress factors affect the accumulation M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 of bioactive compounds and related physiological and biochemical processes.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Liang et al (2012) with minor modifications[34]. The dried hairy roots were ground into powder with a mortar and pestle and sieved through a 0.45-mm screen.…”
mentioning
confidence: 99%